Low Emission Zones for Better Health: Evidence from German Hospitals - Florian Wozny (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper studies health effects from restricting the access of high-emission vehicles to innercities by implementing low emission zones. For identification, we exploit variation in the timing and the spatial distribution of the introduction of new low emission zones across cities in Germany. We use detailed hospitalization data combined with geo-coded information on the coverage of low emission zones. We confirm that low emission zones significantly reduce levels of air pollution in urban areas and that these improvements in air quality translate into population health benefits. We find that the number of diagnoses related to exposure to air pollution is significantly reduced for hospitals located within or in close proximity to a low emission zone after it becomes effective. In particular, the number of diagnosis for diseases of the circulatory and the respiratory system are significantly reduced.
Keywords: I18; Q52; Q53; 330; Low Emission Zone; air pollution; health; Germany